Development of the female reproductive system in the freshwater crayfish Cherax quadricarinatus (Decapoda, Parastacidae) - Vazquez, Fernanda Jimena (2008)
The differentiation of the female reproductive system from a macroscopic and microscopic point of view was studied in Cherax quadricarinatus. For this characterization, 184 females were dissected and processed for the histological analysis. From the differentiation of the ovary up to its maturity, three ovarian morphotypes could be distinguished macroscopically: parallel strands without any contact between them, an H-shaped ovary, and a Y-shaped ovary. These morphotypes were compared within the Astacida. Four ovarian developmental stages were recognized based on ovary color, and the histological structure and relative proportion of cellular types. The post-spawning ovary was also characterized. The components of the female reproductive system sheath were described and its modifications in the ovary and oviducts were determined and compared. Theoretical aspects of the study of sexual differentiation in C. quadricarinatus were discussed within a phylogenetic framework.